Penerapan blue economy dengan budidaya udang vaname (Litopenaeus vannamei) - Sudirman Adibrata; Rahmad Lingga; Mohammad Agung Nugraha (Journal of Tropical Marine Science, 2022)
This research was conducted from December 2021 to February 2022 in Balunijuk Village, Merawang District, Bangka Regency, Bangka Belitung Islands Province. The method used primary and secondary data which was analyzed with a qualitative descriptive approach to policy and vaname shrimp culture. The results showed that designing sustainable development must follow the vision, mission, goals, policies, strategies, programs, to the implementation of activities. One of the priority policies related to food and nutrition action plans or food security was by utilizing marine resources. Food security by utilizing resources from the sea was known as the blue economy concept. Sustainable marine development policies required political effectiveness for the benefit of communities and ecosystems. The application of the blue economy concept with vaname shrimp cultivation in biofloc tarpaulin ponds technically required the measurement of standard parameters such as dissolved oxygen (DO), ammonia (NH3), nitrite (NO2), nitrate (NO3), phosphate (PO4), TDS, brightness, depth, water temperature, salinity, and water pH. Water quality data showed that it could still be tolerated, did not exceed its carrying capacity, and was still in standard water conditions for aquaculture. The implementation of vaname shrimp cultivation in biofloc tarpaulin ponds could increase economic benefits in a sustainable manner, increase healthy products with environmentally friendly technological innovations using Probio_FmUBB probiotics, provide access to small-scale artisanal fisheries, and open market access.